Analisis Customer Relationship Management (CRM) Pada Bisnis Penjualan Sepeda Motor dengan Pengujian Sistem Metode UCD - Fitriany, Armelia Eka; Mulyono, Herry (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Nada Salwa Tour & Travel is a service business operating in the travel sector. Where the current system has obstacles in acquiring new customers, improving relationships with customers, and retaining customers. Based on existing problems, Nada Salwa Tour & Travel requires a web-based Electronic Customer Relationship Management (E-CRM) system that can help Nada Salwa Tour & Travel and customers in establishing good relationships. The aim of this research is to analyze the service relationship between companies and customers and design a web-based Electronic Customer Relationship Management (E-CRM) System to create better relationships between companies and customers through website features. The author implemented an object-oriented system including Use Case diagrams, activity diagrams, class diagrams, System View displays, database structure tables. The result of this research is a web-based E-CRM system that can help solve the problems that exist at Nada Salwa Tour & Travel. The results of testing the design that was created using the cognitive walkthrough method with a total of 5 respondents were learning ability 96.15%, error 1.34%, and efficiency 94.93%.